HER2 Aberrations as a Novel Marker in Advanced Biliary Tract Cancer - Kim, Hongsik; Kim, Ryul; Kim, Hye Ryeon; Jo, Hyunji; Kim, Hana; Ha, Sang Yun; Park, Joon Oh; Park, Young Suk; Kim, Seung Tae (Frontiers in Oncology, 2022)
HER2 aberrations have been reported as a novel biomarker in HER2-directed therapy or as a prognostic marker in various tumor types. However, in advanced biliary tract cancer (BTC), there have been few studies regarding HER2 aberrations as a biomarker. We analyzed 121 advanced BTC patients who had been treated with Gemcitabine/Cisplatin (GP) as a 1st line therapy between November 2019 and April 2021. Next-generation sequencing (NGS), namely, HER2 aberrations was performed in all patients. The TruSight™ Oncology 500 assay from Illumina was used for the NGS panel. Among 121 patients with advanced BTC, HER2 aberrations were observed in 18 patients (14.9%). For subtypes of HER2 aberrations, point mutation was observed in 5 patients (27.8%), gene amplification in 11 patients (61.1%), and both point mutation and gene amplification in 2 patients (11.1%). The frequency of HER2 aberrations was significantly different according to the primary tumor (p = 0.009). In gallbladder cancer, HER2 aberrations were observed at a relatively high frequency (36.4%). The tumor response to GP did not differ between patients with and without HER2 aberrations (33.3%, vs. 26.2%, respectively, p = 0.571). The median progression-free survival (PFS) to GP was 4.7 months (95% CI, 4.0 to 5.5 months) in patients with HER2 aberrations and 7.0 months (95% CI, 5.2 to 8.8 months) without HER2 aberrations (p = 0.776). The median overall survival (OS) was not reached and not reached in patients with and without HER2 aberrations (p = 0.739), respectively. The univariate analysis for PFS to GP and OS showed that HER2 aberrations were not an independent factor for survival. This study showed that the HER2 aberrations were observed in 14.9% of advanced BTC and were not an independent biomarker for survival.